2023
DOI: 10.1111/apa.16807
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis showed that complementary and alternative medicines were not effective for infantile colic

Abstract: Aim Osteopathy and chiropractic techniques are used for babies for different reasons, but it is unclear how effective they are. The aim of this study was to evaluate their effectiveness in reducing crying time and increasing sleeping time in babies with infantile colic. Methods A systematic review and meta‐analysis was conducted on infantile colic studies that used complementary and alternative medicine techniques as interventions. The outcome measures were hours spent crying and/or sleeping. We used the PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Most of them concluded that there was insufficient evidence to support CST in any condition. Our findings are thus in accordance with the previously published evidence [ 1 , 15 , 18 , 57 , 60 ]. Our systematic review and meta-analysis is the first that critically evaluates all the currently available evidence on CST in musculoskeletal and non-musculoskeletal conditions.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Most of them concluded that there was insufficient evidence to support CST in any condition. Our findings are thus in accordance with the previously published evidence [ 1 , 15 , 18 , 57 , 60 ]. Our systematic review and meta-analysis is the first that critically evaluates all the currently available evidence on CST in musculoskeletal and non-musculoskeletal conditions.…”
Section: Discussionsupporting
confidence: 94%
“…Several previous systematic reviews have investigated the effects of CST in different populations [ 1 , 15 , 18 , 19 , 57 , 58 , 59 , 60 ]. Most of them concluded that there was insufficient evidence to support CST in any condition.…”
Section: Discussionmentioning
confidence: 99%
“…5 were compared with no intervention. 6 The meta-analysis comprised five studies with a total of 422 babies. The quality of the evidence was rated as very low for both outcome measures.…”
Section: Why Do We Fear Bottles and Pacifiers?mentioning
confidence: 99%
“…A systematic review and meta‐analysis by Cabanillas‐Barea et al explored the use of osteopathy and chiropractic techniques to treat infantile colic. The authors report that they failed to decrease crying time and increase sleeping time in babies with infantile colic when the results were compared with no intervention 6 . The meta‐analysis comprised five studies with a total of 422 babies.…”
Section: Osteopathy and Chiropractic Techniques Were Not Effective Fo...mentioning
confidence: 99%
“…
We appreciate all the comments made regarding our study 'Systematic review and meta-analysis showed that complementary and alternative medicines were not effective for infantile colic'. 1
…”
mentioning
confidence: 99%